Stereotactic radiofrequency ablation as first-line treatment of recurrent HCC following hepatic resection. Issue 8 (August 2020) - Schullian, Peter; Laimer, Gregor; Putzer, Daniel; Levy, Elliot; Braunwarth, Eva; Stättner, Stefan; Bale, Reto
Abstract: Background: To evaluate the therapeutic efficacy, safety and overall clinical outcome of multiprobe stereotactic RF ablation (SRFA) as first-line treatment of HCC recurrence after hepatic resection (HR). Study design: In this retrospective single-center study, 34 consecutive patients with previous HR were treated by SRFA between 2006 and 2018 for 140 HCCs in 60 ablation sessions. Results: The median treated tumor size was 3.0 cm (range 0.5–10 cm). SRFA was primarily successful for 133/140 (95%) tumors. Four tumors were successfully retreated, resulting in a secondary technical efficacy rate of 97.9%. Local tumor recurrence developed in 4 of 140 tumors (2.9%). The major complication rate was 4.8% (3 of 60 ablations). No periprocedural deaths occurred. The overall survival (OS) rates at 1-, 3-, and 5- years from the date of the first SRFA were 94.0%, 70.2%, and 53.3%, respectively, with a median OS of 69.1 months (95% CI 18.8–119.3). The disease-free survival (DFS) was 52.6%, 19.7% and 15.8%, at 1-, 3- and 5- years, respectively, with a median DFS of 12.8 months (95% CI 9.0–28.9). Conclusion: Stereotactic RFA is a safe, feasible and useful option in the management of recurrent HCC following HR with low morbidity paired with good clinical outcome. Abstract : In this retrospective single-center study, we have shown that stereotactic RFA is a safe, feasible and effective option in the management of recurrent HCC after HR with low morbidity paired with good clinical outcome.